The Hemiplegic Shoulder Pain: A Descriptive Study - Mahayati, Dewi; Ryanto, Agus (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Stroke is the number one cause of disability and the number three cause of death in the world after heart disease and cancer in both developed and developing countries. The disorder that often occurs is weakness in the upper extremities with the main complication being shoulder disorders. Hemiplegic Shoulder Pain (HSP) is one of four complications that often occurs in stroke patients. Research in several countries reports HSP rates of more than 65%. The diagnosis of HSP is difficult to make and is often used to describe a complexity of shoulder problems. Many factors influence the occurrence of HSP, such as immobilization, shoulder impingement, subluxation, spasticity and neuropathic pain. The consequences of HSP are decrease in the functional ability of upper extremity and disturbances in comfort and even sleep disorders which will reduce the quality of life. Physiotherapists play a role in preventing and providing interventions for HSP conditions. Clinical data on the incidence of HSP and the risk factors that cause it are needed to create a comprehensive HSP prevention program and intervention plan. To determine the incidence of HSP and its risk factors in post-stroke patients. Method: This study used descriptive method with a case study design using questionnaires and physical examination. The research subjects were chronic stroke sufferers with onset less than 1 year, totaling 78 people. The questionnaire used contains questions about history of stroke and other conditions related to stroke and shoulder pain. The physical examination and measurements used are the Shoulder Pain and Disability Index (SPADi) to assess the level of pain and disability and the Fugl Meyer Assessment for Upper Extremity (FMA-UE) for upper extremity functional ability. The research was conducted at the Mahar Mardjono National Brain Center Hospital, Jakarta from August to September 2023. Results: This study shows that 77% of stroke sufferers experienced HSP and there was a significant relationship between HSP and levels of pain and disability (p=0.000) as well as decreased upper extremity functional ability (p=0.050). Conclusion: HSP is a complication that often occurs in stroke sufferers and can affect the level of pain and disability and upper extremity functional ability.